Dödsstraffet i USA : Allmänpreventivt eller brutaliserande? - Bergqvist, Martin (Nordisk Tidsskrift for Kriminalvidenskab, 2000)
In 1976, the United States Supreme Court concluded that capital punishment was constitutional, and since then 570 persons have been executed in the USA. The number of executions per year has increased substantially during the last decade, and there is reason to believe that the excessive use of the death penalty will continue. This article focuses on only one of many debated issues regarding the death penalty, namely its potential effect on the homicide rate. Initially, the arguments concerning the effect are discussed and thereafter the empirical findings supporting these arguments are reviewed. In the ongoing debate, two contradictory arguments have been used. Death penalty proponents argue that it decreases the number of homicides through deterrence. Opponents, on the other hand, argue the hypothesis of brutalisation, which predicts the opposite, i.e. the death penalty increases the number of homicides. Given that the number of studies testing these hypotheses is immense, this article will not cover the total literature, but rather focus on studies purporting to find evidence of either a deterrent or a brutalisation effect. Following the review it is argued that the methodological problems in this area of research are extensive. The data used are not robust enough to transcend methodological approaches, so the choice of method most likely has an impact on the results obtained. When demanding that a substantively significant result should survive different statistical tests, the author comes to the conclusion that the research conducted has not presented any conclusive evidence supporting either the argument of deterrence or that of brutalisation.